Penerapan Metode Berpikir Desain Dalam Merancang Ide Desain Nowast Planner - Aisyah, Sitti Nur; Setiawan, Hayun; Muslim, Liqo RifatifatuL; Alghifari, Mochamad Nur Tsani Ihsan; Zein, Muhammad Arsyad; Pujangga, Didar (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2025)
A well-designed planner can significantly aid users in achieving their goals more easily and enjoyably. Engaging and functional designs can motivate consistent use. This study examines the impact of visually appealing and user-friendly planner designs on user motivation. It references findings by Poppy Sharples and Carolyn Parkinson, indicating that structured planners with ample space help users organize time and activities more effectively. The design thinking method is employed in creating the Nowast Planner concept. This approach is chosen for its human-centered focus, allowing for the collection of subjective and objective insights in decision-making. The research involves four design thinking stages: empathize, define, ideate, prototype, and test. The goal is to apply design thinking to develop innovative and beneficial planner ideas. The study aims to produce design concepts that can be developed into tangible products, aiding users in achieving their goals more systematically. It finds that integrating the Eisenhower Matrix into planner design helps users categorize and manage tasks based on importance and urgency. The prototype is tested with potential users to gather feedback for further development.